Analysis Influence of NPL, Good Corporate Governance, and BOPO to Stock Prices on National Private Bank Period 2012 - 2018 - Agustinus Winoto; Hendryan Tua Marudut Purba (Bina Nusantara University, 2022)
The level of performance of a bank has many factors that affect that stock prices, including internal factor from the bank itself. The purpose of this research is to analyse the Non-performing Loan, Good Corporate Governance, and Beban Operasional Pendapatan Operasional (BOPO) affect to stock prices simultaneously or partially on the national private private banks listed on the Indonesia Stock Exchange period 2012-2018. The sample in this study was 21 national private banks listed on the Indonesia Stock Exchange period 2012-2018. Data analysis model used is panel data regression using the software E-views 10. The results of this study indicate simultaneously the independent variables namely NPL, GCG and BOPO have a significant effect on stock prices in national private banks period 2012-2018, NPL have a significant effect on stock prices at national private private banks period 2012-2018, whereas GCG and BOPO do not significant effect on stock prices on the national private private bank period 2012-2018.